The epidemiological profile of leprosy hospitalizations in Brazil from 2018 to 2023 (Research, Society and Development, 2024)
Leprosy is a chronic disease whose causative agent is Mycobacterium leprae, a bacterium capable of affecting the skin and peripheral nerves. To analyze the epidemiological profile of leprosy hospitalizations in Brazil from 2018 to 2023. This is an ecological, descriptive, quantitative study, carried out by collecting secondary data, available on the website of the Department of Information Technology of the Unified Health System (DATASUS) and the TABNET application, through information from the SUS Hospital Information System (SIH/SUS) of hospitalizations according to the ICD - 10 morbidity list: Leprosy (Leprosy) and Sequelae of leprosy (Leprosy). The data was searched in August 2024. The epidemiological profile of leprosy hospitalizations in Brazil revealed a total of 16,300 hospitalizations. The Northeast region accounted for 6,543 hospitalizations, equivalent to 40.14% of the total. The age group affected was 40 - 49 years old, male and of brown race/color. It is worth highlighting the importance of regional disparities in Brazil and how socio-economic factors impact on the prevalence and severity of leprosy, especially in the North, Northeast and Central-West regions. It is essential to emphasize that, despite public policies and control efforts, leprosy remains a neglected disease, with significant gaps in epidemiological data and in the proper management of associated physical disabilities. These factors suggest the need for more intensive training for health professionals, as well as more effective strategies and actions for active search and early diagnosis, especially in the most vulnerable areas.